Redox Regulation of EGFR Signaling Through Cysteine Oxidation() - Truong, Thu H. (2012)
Epidermal growth factor receptor (EGFR) exemplifies the family of receptor tyrosine kinases that mediate numerous cellular processes including growth, proliferation and differentiation. Moreover, gene amplification and EGFR mutations have been identified in a number of human malignancies, making this receptor an important target for the development of anticancer drugs. In addition to ligand-dependent activation and concomitant tyrosine phosphorylation, EGFR stimulation results in the localized generation of H(2)O(2) by NADPH-dependent oxidases. In turn, H(2)O(2) functions as a secondary messenger to regulate intracellular signaling cascades, largely through the modification of specific cysteine residues within redox-sensitive protein targets, including Cys797 in the EGFR active site. In this review, we highlight recent advances in our understanding of the mechanisms that underlie redox regulation of EGFR signaling and how these discoveries may form the basis for development of new therapeutic strategies to target this and other H(2)O(2)-modulated pathways.